Evaluation of the toxicity of superfine materials to change the physiological functions of aquatic organisms of different trophic levels. Issue 1 (October 2015) - Morgalev, S; Morgaleva, T; Gosteva, I; Morgalev, Yu
Abstract: We assessed ecological and biological effects caused by the physical and chemical properties of nanomaterials on the basis of the laboratory researches into water test-organisms of different trophic levels. We studied the physiological functions of water organisms on adding into the environment superfine materials of various chemical nature and structural characteristics: metallic nanoparticles of nikel (nNi), argentum (nAg), platinum (nPt), aurum (nAu), binary NPs (powder of titanium dioxide – nTiO2, aluminum oxide – nAl2 O3, zink oxide – nZnO, silicon nitride – nSi3 N4, silicon carbide (nSiC) and carbon nanotubes (BT-50, MCD- material). We observed the dependence of developing the complex of unfavourable biological effects in water plants and entomostracans' organisms on the physical and chemical properties of superfine materials. We determined the values of NOEC, L(E)C20 and L(E)C50 for aquatic organisms of various regular groups. We found out the most vulnerable elements of the communities' trophic structure and the possibility of a breakdown in the water ecosystem food pyramid.